E-Recruitment Menggunakan Metode Simple Additive Weighting dan Algoritma K-Nearest Neighbor - Janubiya, Tasya Khaerani; Andryana, Septi; Sholihati, Ira Diana (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Along with the increasing number of PT Midi Utama Indonesia Tbk outlets, the company's human resource needs are also increasing. Therefore, the recruitment of new employees is very important to support the company's operations. In order to select prospective new employees to fill various positions needed by the company. Recruitment of new employees has not been carried out professionally. This is because there is no systematic method to assess the suitability of new employees. The application of a decision support system uses a combination of the Simple Additive Weighting (SAW) method and the K-Nearest Neighbor (K-NN) algorithm. This method determines the weight value and ranking results of each candidate. Then, the company conducts the process of selecting candidate data based on the value closest to the old prospective employee to determine the final classification results. In this case, prospective new employees who qualify as employees are based on predetermined criteria. Then this decision support application is built using the PHP programming language and MySQL database. The conclusion in this study by combining the SAW and K-NN methods in the recruitment process is very helpful because the administrative and assessment processes are carried out online. So that decision makers can make choices quickly and accurately.